Time for a change: is idiopathic pulmonary fibrosis still idiopathic and only fibrotic?. Issue 2 (February 2018) - Wolters, Paul J; Blackwell, Timothy S; Eickelberg, Oliver; Loyd, James E; Kaminski, Naftali; Jenkins, Gisli; Maher, Toby M; Molina-Molina, Maria; Noble, Paul W; Raghu, Ganesh; Richeldi, Luca; Schwarz, Marvin I; et al.
Summary: Idiopathic pulmonary fibrosis (IPF) is a progressive, irreversible, and typically fatal lung disease characterised by subpleural fibrosis, subepithelial fibroblast foci, and microscopic honeycombing. Although understanding of the pathogenic mechanisms continues to evolve, evidence indicates that distal airway and alveolar epithelial cells are central drivers of the disease. In this Viewpoint, we review the history of naming and classifications used to define the disease now referred to as IPF, in the context of understanding the clinical presentation, causes, and pathogenesis of the disease. We aim to generate discussion on whether, given the substantial progress made in understanding the clinical, genetic, cellular, and molecular mechanisms involved in the development of IPF, a change of name should be considered. To initiate this discussion, we offer new suggestions to update the name of this disease and new approaches to classify all forms of pulmonary fibrosis.